Strategi Coping Stres Konselor pada Era New Normal - Kholisah, Hafidzah; Majo, Happy Karlina (Guidance and Counseling Study Program, Pattimura University, 2023)
The Covid-19 pandemic has had various impacts, one of which is stress. One of these things happened to the counselor. The purpose of this study is to describe how counselor’s stress coping strategies work in the new normal era. The research method used is descriptive qualitative method. In collecting data by way of observations and interviews which are then processed data. The results of this study are that there are two forms of stress coping strategies, namely emotional focused coping and problem focused coping. The stress coping strategy carried out by counselors in the new normal era is by using emotional focused coping. Actions taken include self-control, accepting responsibility and positive reapraisal. The purpose of the counselor is to do a coping stress to reduce anxiety and worry about the problems faced, especially after the pandemic and entering the new normal era of adaptation.